More information, lower price? Access to market-based reference prices and gains in public procurement efficiency - José Martinez-Carrrasco; Otávio Canozzi Conceiç\~ao; Ana Lucia Dezolt (Inter-American Development Bank (IDB), 2023)
The paper examines the impact of providing market-based reference prices on public procurement efficiency in Brazil. Specifically, the study focuses on the State Secretariat of Health (SES) in Rio Grande do Sul and the algorithm developed by the local tax administration to calculate representative reference prices for pharmaceutical products. Unlike previous studies, reference prices are calculated based on the universe of local business-to-business transactions. The study finds that SES procurement officers' access to this information caused a significant reduction in purchase unit prices, particularly for products characterized by a higher ex-ante unit price, a smaller number of suppliers, and purchased by a smaller number of public institutions. The gains in efficiency are attributed to the use of up-to-date market information, which is particularly useful for products where information asymmetry is more likely to exist between procurement officers and private providers.
Keywords: D40; H51; H57; 330; Public procurement; reference prices; electronic invoicing; Brazil